Agricultural Waste or Residue as Adsorbent for Nickel Removal - Aznan, Muhammad Firdaus (Universiti Teknologi PETRONAS, 2016)
In today’s world, water scarcity affects every corners of the world. More than 1.2 billion people do not have access to clean water resources. This problem happens due to several reasons such as climate changes, natural disaster, contamination of water catchment area and many more. Since water is a basic necessity for living organism to live, a sustainable solution to water deficiency should be think of to avoid the same problem from happening continuously. In order to materialized the solution, thorough research on adsorption should be pursued to clean out contaminated water as it is a valuable resource. The solution should use adsorbents that are as cheap as possible to make it sustainable throughout the process. The objective of this research is to find out the characteristic of agricultural waste or residue (corn cob) to be used as adsorbents, to find out the parameters that can affects the performance of adsorbents, to calculate the effectiveness of each adsorbents to remove nickel ions from water and to find out economical potential of the adsorbent.